A Cross-Sectional Study Among Stroke Survivors of the Indian Himalayan Region Assessing Motor Function, Quality of Life, Depression, and Anxiety - Suman; Yadav, Raj Kumar; Bhadoria, Ajeet Singh; Das , Hrishikesh; Neyaz, Osama (Indian Journal of Community Health, 2025)
Stroke impacts 16 million people annually worldwide, often resulting in lasting disabilities and psychological complications such as depression and anxiety, affecting the quality of life. This study assessed the motor function, depression, anxiety, and quality of life among stroke survivors in the Indian Himalayan region, with their sociodemographic profile. 164 stroke patients were examined at a tertiary teaching hospital. The sample was predominantly male (70%), with an average age of 50.61 years. Motor Assessment Scale scores indicated poor motor function (mean = 12.05), while Stroke-Specific Quality of Life Scale scores revealed low quality of life (mean = 91.71). On Beck Depression Inventory and Beck Anxiety Inventory, 36% of participants had severe depression while, 20.7% had moderate anxiety levels. As the study indicated a high prevalence of severe depression and anxiety, affecting also the motor functions and quality of life, addressing the psychological issues is critical for improving rehabilitation outcomes and overall well-being among stroke survivors.